Redistribution of sputtered material in a plane ion-plasma system with an abnormal glow discharge - Kuzmichev, A.I.; Melnichenko, M.S.; Shinkarenko, V.G.; Shulaev, V.M. (Вопросы атомной науки и техники, 2020)
The redistribution of the flow of sputtered material of a target (cathode) between the collector and the target in a plane–parallel electrode system with an anomalous glow discharge is analyzed in the kinetic approximation. Sputtering is the result of bombardment of the target by gas ions accelerated in the near–cathode space charge layer and by fast neutral atoms formed as a result of resonant ion charge exchange. Sputtered atoms partially return to the target due to collisions with gas molecules. The formulas were obtained, which were confirmed in the experiment that makes it possible to correctly estimate the ratio of the sputtered material flows deposited on the collector and the target. The results of the work are used to calculate the parameters of the processes of coating deposition and ion cleaning of the target under conditions of the anomalous glow discharge. Аналізується в кінетичному наближенні перерозподіл потоку розпиленого матеріалу мішені (катода) між колектором і мішенню в плоскопаралельній електродній системі з аномальним тліючим розрядом. Розпилення є результатом бомбардування мішені газовими іонами, прискореними в катодному шарі просторового заряду, і швидкими нейтральними атомами, що утворюються в результаті резонансного перезарядження іонів. Розпилені атоми частково повертаються на мішень через зіткнення з газовими молекулами. Отримано формули, підтверджені в експерименті, які дозволяють коректно оцінити співвідношення потоків розпиленого матеріалу, що осідають на колекторі і мішені. Результати роботи використовуються для розрахунку параметрів процесів нанесення покриттів і іонної очистки мішені в умовах аномального тліючого розряду. Анализируется в кинетическом приближении перераспределение потока распылeнного материала мишени (катода) между коллектором и мишенью в плоскопараллельной электродной системе с аномальным тлеющим разрядом. Распыление является результатом бомбардировки катода–мишени газовыми ионами, ускоренными в прикатодном слое пространственного заряда, и быстрыми нейтральными атомами, образующимися в результате резонансной перезарядки ионов. Распылeнные атомы частично возвращаются на мишень из-за столкновений с газовыми молекулами. Получены формулы, подтвержденные в эксперименте, что позволяет корректно оценить соотношение потоков распыленного материала, осаждающихся на коллекторе и мишени. Результаты работы используются для расчета параметров процессов нанесения покрытий и ионной очистки мишени в условиях аномального тлеющего разряда.